2006
DOI: 10.1289/ehp.8998
|View full text |Cite
|
Sign up to set email alerts
|

Saxitoxin Puffer Fish Poisoning in the United States, with the First Report of Pyrodinium bahamense as the Putative Toxin Source

Abstract: BackgroundFrom January 2002 to May 2004, 28 puffer fish poisoning (PFP) cases in Florida, New Jersey, Virginia, and New York were linked to the Indian River Lagoon (IRL) in Florida. Saxitoxins (STXs) of unknown source were first identified in fillet remnants from a New Jersey PFP case in 2002.MethodsWe used the standard mouse bioassay (MBA), receptor binding assay (RBA), mouse neuroblastoma cytotoxicity assay (MNCA), Ridascreen ELISA, MIST Alert assay, HPLC, and liquid chromatography-mass spectrometry (LC-MS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 35 publications
4
99
0
Order By: Relevance
“…bahamense, considered potentially toxic only due to a single report on the toxicity of var. bahamense in the coastal waters of East Florida (Landsberg et al 2006), reached the population density of 1.8x10 5 cells l -1 ). In total, 18 potentially toxic species (16 dinoflagellates and two cyanobacteria) were found.…”
Section: Study Area and Samplingmentioning
confidence: 97%
“…bahamense, considered potentially toxic only due to a single report on the toxicity of var. bahamense in the coastal waters of East Florida (Landsberg et al 2006), reached the population density of 1.8x10 5 cells l -1 ). In total, 18 potentially toxic species (16 dinoflagellates and two cyanobacteria) were found.…”
Section: Study Area and Samplingmentioning
confidence: 97%
“…In Florida's marine waters (USA), puffer fish have been confirmed to be a hazardous reservoir of STX 17 and this toxin was responsible for 28 poisoning cases between 2002 and 2004 8 . A study in Brazil identified saxitoxin and gonyautoxin as the components responsible for toxicity in Colomesus asellus, a freshwater puffer fish 23 .…”
Section: Discussionmentioning
confidence: 99%
“…STX is produced by microalgae 8 . STX accumulates by feeding on bivalves that have ingested toxic dinoflagellate such as Alexandrium tamarense 19 and Pyrodinium bahamense 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main symptoms of human intoxications associated with PFP and PSP include neurological, cardiac and gastrological complications. Numbness of the mouth, face and fingertips, nausea and vomiting, paralysis of the arms and legs, difficulty in breathing and eventually -for extreme cases -death associated with respiratory paralysis have been described (Landsberg et al 2006;Schantz and Johnson 1992). For more information see Chap.…”
Section: Tetrodotoxins and Saxitoxinsmentioning
confidence: 99%